Chronic Suppurative Otitis Media of Auricle Dextra Sinistra: Case Report - Ikhsani, Arryza; Soesanto, Bambang (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Chronic suppurative otitis media (CSOM) is a chronic infection of the mucoperiosteum and osseous tissue of the middle ear, characterized by perforation of the tympanic membrane and a distinctive symptom of otorrhea. Globally, this disease affects a considerable number of individuals, ranging from 65 to 330 million. The majority of those affected reside in less developed countries. The aim of this case report is to provide a comprehensive understanding of CSOM. This study includes a literature review sourced from various databases over the past 10 years. The case report discusses a 65-year-old female patient with chronic suppurative otitis media from history taking to the therapy given. Chronic suppurative otitis media is often characterized by ear discharge (otorrhea) and hearing loss. Accurate diagnosis is crucial to prevent complications and improve healing prospects.